Surgical treatment of laryngeal stenosis with semiconductor laser - Chernokur A.A. (Medičnì Perspektivi)
The article reflects the current trends in the treatment of diseases of the larynx, accompanied by stenosis and impaired fonatory function, such as laryngeal papillomatosis and double-sided paresis of the recurrent larynx nerve. Actuality of surgical treatment of bilateral paresis of the recurrent larynx nerve is due to the fact that a significant proportion of patients with this disease are persons of vocal professions and functional result of the operation determines the quality of life, professional suitability. Using semiconductor laser causes a good functional outcome in this pathology treatment. The aim of the study was to improve the effectiveness of treatment of patients with laryngeal papillomatosis and with bilateral paresis of the recurrent larynx nerve. All patients underwent surgery with using semiconductor laser "Lika - surgeon." Results of treatment made it possible to draw a conclusion that microlaryngoscopy with laser vaporization of papillomas can reduce frequency of relapses by 15.4% during the first year after surgery as compared to the control group. Using of semiconductor laser in patients with bilateral paresis of the larynx allows to more effectively restore compensated breathing through upper airways as compared with the control group. Application of laser in phonosurgery allow to save a good voice function in 76.9% of patients.